Practising evolution: Theory for understanding and evaluating participatory research - Loevinsohn, Michael E. (International Service for National Agricultural Research, 1998)
Research and development that aim to stimulate farmers' experimentation demand something of a paradigm shift. Such "collegial" or "empowering" participation requires altered attitudes, new skills and changed incentive structures. But what is there to impel people and their institutions to make these changes? This paper addresses one factor: the lack of a theoretical understanding to guide the development of participatory research and help to situate it in science. The theory required is one that is useful in real time, that helps R&D workers make better choices. Participatory or not, applied research is the search for effective solutions to real world problems, in as efficient a manner as possible. Scientists working in a conventional mode can draw on a large body of theory validated by experience when they design their research. Researchers contemplating PR also confront design choices, though of a fundamentally different nature: they can at most influence the research process, not unilaterally control it. Unfortunately, in the absence of useful theory, observations about the effectiveness of design choices are made independently of each other. There is little basis for accumulating experience and predicting what will work. There is no means to assess the trade-offs or synergies that might result from different design choices. What is needed is a framework that would help to organize observations, suggest hypotheses about what will work and show how these can be tested in practice. This paper argues that evolutionary theory can provide a good part of the needed framework. It first describes how evolution can be used to explain the processes of change in agricultural systems. It then shows the relationship between the design choices of PR and the principal parameters of evolutionary dynamics. Finally it shows how the effects of design choices made by PR initiatives can be assessed, using examples from Kenya and Rwanda.